Synthesis and Characterization of Oxovanadium(IV) Complexes Derived from Schiff Bases - Ahmad Khan, Shuyeb; Saxena, Sharad (Asian Journal of Chemistry, 2010)
Schiff bases like 5-chloro salicylaldehyde morpholine N-thio hydrazone (SMTH), butyrophenone semicarbazone (BSC), 3-hydroxy benzaldehyde isonicotinic acid hydrazone (HBINAH) and bis(2-hydroxy-1-napthaldehyde) malonyl dihydrazone BNHMDH are formed by the condensation of different carbonyl and amino compounds. The complexes of these Schiff bases of VO(IV) have been synthesized and characterized by elemental analyses, molar conductance, infrared and electronic spectral studies.